Relationship between perception of parental communication styles incompatibility amongst high school students - Mohammad Akbari Booreng (Gonabad University of Medical Sciences, 2017)
Family is an influential setting in physical and mental health of children and adolescents. Accordingly, studying the atmosphere and current relationships in the family in terms of their effect on children and adolescents is highly necessary. This study was designed and conducted to investigate the relationship between students' perception of parental communication styles and their own incompatibility. In this descriptive study, population consisted of female students of high school, of whom, 300 were selected and studied in a random cluster method. Data were collected using the standardized students' compatibility and family communication pattern questionnaire. The results showed a significant relationship only between emotional incompatibility and conformity communication orientation. A statistically significant relationship was also observed between general incompatibility and conformity communication orientation. The results also showed that parental communication styles have a role in children's incompatibility. Analysis of each dependent parameter alone showed a difference in parental communication styles only in emotional incompatibility component. Pluralistic family communication style is associated with emotional compatibility of children of the family. The present study results relating to role of communication styles in students' compatibility suggest that it is necessary to teach parents appropriate communication styles.